Current chromatographic methods to determine cannabinoids in biological samples: A review of the state-of-the art on sample preparation techniques - Igor Gustavo Carvalho Oliveira; Caroline Fernandes Grecco; Israel Donizeti de Souza; Maria Eugênia Costa Queiroz (Green Analytical Chemistry)
Cannabidiol (CBD) and Δ9-tetrahydrocannabinol (THC) are the primary compounds of interest in the plant cannabis sativa, used mainly as recreational drug. Since THC, CBD, and other cannabinoids were discovered, they have been investigated as potential therapeutic agents for numerous pathologies, including neurodegenerative disorders, cancer, pain, inflammation, and autoimmune conditions. In this context, developing chromatographic analytical methods to determine THC, CBD, their metabolites, and other cannabinoids in biological samples is essential in the forensic field, to detect illicit use of cannabis, and medical field, to prospect pharmaceutical applications of cannabinoids and cannabis-based products. Because biological matrixes are complex, these compounds cannot be directly analyzed on chromatographic systems, and a sample preparation step is required. In this step, an extraction technique is used to exclude interfering molecules while selectively extracting and pre-concentrating the target analytes, often present at trace levels in biological samples. This paper reviews the chromatographic methods published over the past two years and highlights sample preparation. Special focus is placed on state-of-the-art sample preparation techniques aimed at determining CBD, THC, and their metabolites. Moreover, this review discusses fundamentals, details, pros and cons, and intrinsic parameters of classic, conventional sample preparation techniques as well as modern, miniaturized, and microextraction techniques. Additionally, this review covers the reported biological matrixes, instrumentation, and applications.